Le projet de paysage au service de la valorisation d’un jardin historique - Chiara Santini; Agnès Juvanon du Vachat (Projets de Paysage, 2011)
This contribution offers to analyse the reasoning and the stakes of the landscape appraisal in its relationship with historical gardens. It consists in showing that this appraisal can be a tool at the service of the promotion of a place. By taking the Tuileries Garden in Paris as case study, we shall point out how the landscape project permits the historical identity of a given place to be preserved as well as adapting it to the modern-day demands. The important historical, identity, and symbolic heritage of this garden turns it into a privileged analysing field at the moment of judging the heritage value of a site. Moreover, the Tuileries Garden has been the object of an ambitious renovation project at the end of the 20th century, led by landscapers Pascal Cribier and Louis Benech. We will have a critical reading of this project, and we will highlight the economic ans environmental issues which it fulfilled.